How Digital Marketing Research Trends Over Time: A Bibliometric Analysis on Scopus Database - Muttaqien, Zaenul; Hermawan, Agus; Handayati, Puji (PT FORMOSA CENDEKIA GLOBAL, 2024)
The digital era has revolutionized marketing practices, particularly through social media and mobile platforms, profoundly impacting consumer behavior and business strategies. Extensive research underscores the pivotal role of digital marketing in fostering customer relationships and driving business growth. Based on the gathered metadata, bibliometric analysis evaluates the effectiveness of scientific publications. This study investigates the following topics: (1) the total number of articles published by year; (2) the journal in which the author published the article; (3) the affiliation of the researcher who published the article; (4) the nation in which the researcher published the article; and (5) the researcher's field of study. Data in the form of scientific publications written in the English language were gathered between 2003 and 2024 from the Scopus database using the keyword